2001
DOI: 10.1046/j.1365-2044.2001.02132.x
|View full text |Cite
|
Sign up to set email alerts
|

A mixture of alfentanil and morphine for rapid postoperative loading with opioid: theoretical basis and initial clinical investigation

Abstract: SummaryPharmacokinetic modelling of estimated central nervous system concentrations was used to devise the optimal mixture of morphine and alfentanil for the treatment of postoperative pain. Modelling revealed that an intravenous opioid pain protocol using an alfentanil2morphine mixture in the proportions 0.75 : 10 mg would provide a profile of analgesia of rapid onset, yet slow offset. The regimen was evaluated in 58 patients in the recovery ward who were randomly allocated to receive analgesia using pain pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Dosing in Group AM was based on a previous study which used pharmacokinetic modelling to determine the optimal ratio of alfentanil to morphine for analgesia and then tested this model in the postanaesthesia care unit (PACU). 9 Dosing in Group F was consistent with routine practice and standard protocols at both hospitals.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Dosing in Group AM was based on a previous study which used pharmacokinetic modelling to determine the optimal ratio of alfentanil to morphine for analgesia and then tested this model in the postanaesthesia care unit (PACU). 9 Dosing in Group F was consistent with routine practice and standard protocols at both hospitals.…”
Section: Methodsmentioning
confidence: 82%
“…In the postoperative anaesthesia care unit, a combination of alfentanil and morphine has more rapid onset and a similar duration of effect, along with a comparable sideeffect profile, than does morphine alone. 9 In the first 24 h after Caesarean section, women reported that the opioid combination in PCA, compared with morphine alone, resulted in more rapid onset and greater efficacy after each bolus, with no difference in analgesia duration or overall patient satisfaction. 10 Combining opioids may produce both rapid onset analgesia with timely control of incident pain allowing return to sleep, and longer duration of effect, leading to consolidated periods of sleep with fewer pain-related awakenings.…”
mentioning
confidence: 99%
“…There are only 2 studies looking at pure agonist opioid mixtures for PCA in the literatue 13,14 . The first study examined a combination of morphine and alfentanil for PCA use after caesarian section.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of morphine with the more rapidly, but shorter acting opioid, alfentanil, has been shown to improve analgesic profile and patient satisfaction with PCA in the postoperative setting. 1,2 The Acute Pain Service at the Royal Adelaide Hospital (RAH) developed a protocol to investigate a combination of morphine sulfate 0.8mg/mL and alfentanil hydrochloride 55mg/mL in a double-blind crossover comparison with morphine sulfate 1mg/mL in PCA for pain associated with dressings in burns patients. The RAH pharmacy department was approached to prepare and blind syringes of the trial medications.…”
Section: Introductionmentioning
confidence: 99%